(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
There are certain groups of human beings which are either by nature or because of deep routed custom are weak and vulnerable. They include a child, women, disabled persons, aged person or person belonging to a particular race. In these groups a child comes at the first place. The condition of majority of children is far from satisfactory. From statistical point of view, 21 (about 2 million) of all child deaths under 5 years of age in India. About thirty one out of one thousand children die under one year of age in our country per year.Elaborate legal provisions have been made to protect child’s right in India. There were same laws before independence which were enacted to prevent child marriage and child labour. However, after independence, special attention has been laid for all corner development of the child. The Constitution made specific provisions for child development. Now, Article 21-A has been inserted in it to declare primary education as a fundamental right upto 14 year of age.Despite several legal protections to the rights of children, abuse of their right is on the rise. The National Crime Records Bureau has in its Report an crimes against Children has recorded that in 2017, the maximum number of cases of crime against children involved kidnapping and abduction. International community has also been interested in the protection of child’s right. The United Nations has also accelerated the progress of the child. In its various Conventions, the International body casts a duty on every state to protect child’s rights.